في معهد خادم الحرمين الشريفين بندا أتشيه Google Meet تعليم النحو عبر - Firda, Raihan; Muzaffar, Asyraf; Fajriah, Fajriah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2021)
The using Google Meet as a new platform for the learning process and the obstacles for teachers and students when using it.This research aims to discover: 1) Learning process of Nahwu Study via Google Meet in Ma’had Khadimul Haramain Asy-Syarifain Banda Aceh. 2) Problems faced by teachers and students in learning Nahwu Study via Google Meet in Ma’had Khadimul Haramain Asy-Syarifain Banda Aceh. This research is of analytical descriptive type. Samples of this research are 56 girl students from Akhwat class. The research methods employed are direct observation and interviews. The results of this research are: 1) Learning process of Nahwu Study in Ma’had Khadimul Haramain Asy-Syarifain Banda Aceh implement the direct method, lecturing method, reading method, question-and-answer, and deductive method, which means Nahwu learning method by explaining the rules first followed by examples. Teachers also utilize Power Point to explain I’rab materials, Microsoft Word as a whiteboard, Google to search for sources for pictures of difficult Mufradat, and a PDF book of Arabic language as the source materials of Nahwu Study. However, problems faced by teachers in teaching Nahwu via Google Meet are: 1) Internet connection 2) difficulty in supervising students 3) passive students 4) difficulty in evaluating the study. Furthermore, problems faces by students in learning Nahwu via Google Meet are : 1) internet connection 2) internet quota 3) lack of learning focus 4) lack of learning spirit 5) difficulty in understanding the lessons 6) too many students in one class.